Strategi Penenun dalam Mempertahankan Ulos Motif Silindung di Kabupaten Tapanuli Utara - Thrisia Yohana Sitohang; Roida lumbantobing; Harisan Boni Firmando (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the existence strategy for motif weaving. Silindung. This research was carried out using a qualitative approach that leads to descriptive methods, with a focus on an in-depth understanding of the meaning of ulos and the existence strategies used by weavers. Data was obtained through in-depth interviews with weavers, tourism actors and local communities. Participatory observation was also carried out to gain a more comprehensive understanding of ulos production practices and their role in community life. The collected data was analyzed qualitatively by identifying thematic patterns and describing the results of interviews and observations. The development strategy implemented is a social capital model that involves the Government, Academics, Local Communities, Tourists and the Media in efforts to be involved in developing ulos products which focus on the meaning of ulos, improving production quality, as well as promotion through various channels, including social media. The impact of this existence strategy can be seen in the increase in interest in purchasing ulos in the last 3 years. This research contributes to uncovering the potential of traditional ulos weaving as a cultural and economic asset, as well as providing practical guidance for weavers, the government and buyers. Apart from that, this research also provides new insight into the meaning of ulos and the existence strategies used by weavers in the Silindung rural area.